Feasibility and Acceptability of a Student-Led Lifestyle (Diet and Exercise) Intervention Within a Residential Rehabilitation Setting for People With Severe Mental Illness, GO HEART (Group Occupation, Health, Exercise And Rehabilitation Treatment) - Korman, Nicole; Fox, Harley; Skinner, Tina; Dodd, Cassandra; Suetani, Shuichi; Chapman, Justin; Parker, Stephen; Dark, Frances; Collins, Cheryl; Rosenbaum, Simon; Siskind, Dan (Frontiers in Psychiatry, 2020)
Purpose People with severe mental illness (SMI) experience poor physical health and premature mortality, contributed significantly by modifiable lifestyle risk factors such as poor nutrition, low cardiorespiratory fitness, and physical inactivity. Lifestyle interventions can reduce cardiometabolic risk and confer a range of other positive mental and physical health benefits. We assessed the feasibility, acceptability, safety, and preliminary effectiveness of a lifestyle (combined dietary and exercise) intervention lead by senior exercise and dietetics students in a residential mental health rehabilitation setting. Design Single arm, prospective study evaluating outcomes pre and post a 10-week dietary and exercise intervention. Method People with SMI from three residential rehabilitation units participated in a mixed aerobic and resistance training exercise intervention three times per week that was combined with a dietary intervention (six individual and group sessions). Primary outcome considerations were feasibility (recruitment, retention, and participation rates), acceptability, and adverse events. Secondary outcomes were preliminary effectiveness; (functional exercise capacity, volume of exercise, and metabolic markers), psychiatric symptoms, quality of life, and attitudes to exercise. Results Forty-two participants were recruited (92% primary diagnosis of schizophrenia). Intervention feasibility was supported by high levels of recruitment (68%), retention (77%), and participation (70% exercise, 65% diet sessions); and the absence of serious adverse events. Significant improvements in functional exercise capacity, volume of exercise, general psychiatric symptoms, and negative psychotic symptoms occurred. Anthropometric and metabolic blood markers did not change. While the intervention was acceptable to participants, motivation for and perceived value of exercise reduced over 10 weeks. Conclusions A brief pragmatic student-led lifestyle intervention integrated into usual mental health care was feasible, acceptable, safe, and scalable across two additional mental health residential rehabilitation sites, and resulted in physical and mental health improvements. Increased frequency of dietary sessions and length of dietary intervention may improve metabolic outcomes in the future. People with SMI living in residential rehabilitation units should have access to lifestyle programs to address modifiable lifestyle risk factors. While this brief intervention was feasible and acceptable, this study highlights some of the challenges associated with maintaining motivation for healthy lifestyles for people with SMI. Longer term investigation of real-world lifestyle interventions is warranted, together with additional interventions that may support people with SMI to sustain motivation to address lifestyle factors. Clinical Trial Registration The trial was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR), Unique Identifier: ACTRN 12618000478213, http://www.anzctr.org.au Universal trial number (UTN)—U1111-1211-4009.